Presynaptic nanodomains : a tale of two synapses - Wang, Lu-Yang (2015)
Here we summarize the evidence from two “giant” presynaptic terminals—the squid giant synapse and the mammalian calyx of Held—supporting the involvement of nanodomain calcium signals in triggering of neurotransmitter release. At the squid synapse, there are three main lines of experimental evidence for nanodomain signaling. First, changing the size of the unitary calcium channel current by altering external calcium concentration causes a non-linear change in transmitter release, while changing the number of open channels by broadening the presynaptic action potential causes a linear change in release. Second, low-affinity calcium indicators, calcium chelators, and uncaging of calcium all suggest that presynaptic calcium concentrations are as high as hundreds of micromolar, which is more compatible with a nanodomain type of calcium signal. Finally, neurotransmitter release is much less affected by the slow calcium chelator, ethylene glycol tetraacetic acid (EGTA), in comparison to the rapid chelator 1,2-bis(o-aminophenoxy)ethane-N,N,N’,N’-tetraacetic acid (BAPTA). Similarly, as the calyx of Held synapse matures, EGTA becomes less effective in attenuating transmitter release while the number of calcium channels required to trigger a single fusion event declines. This suggests a developmental transformation of microdomain to nanodomain coupling between calcium channels and transmitter release. Calcium imaging and uncaging experiments, in combination with simulations of calcium diffusion, indicate the peak calcium concentration seen by presynaptic calcium sensors reaches at least tens of micromolar at the calyx of Held. Taken together, data from these provide a compelling argument that nanodomain calcium signaling gates very rapid transmitter release.